Very high cycle fatigue on gas metal arc butt-welded AA6061-T6 plates - 김익수; Moon G. Lee; 전병국; Jungho Cho; 전용호 (Journal of Mechanical Science and Technology, 2023)
In the automobile industry, there is a push to maximize the mileage of electric vehicles by using lightweight materials. Hence, the use of welded aluminum in electric vehicles is increasing, and there is a clear need for detailed characterization of the fatigue life of these welded parts. In this study, gas metal arc welded AA6061-T6 specimens were fabricated and an ultrasonic fatigue test method for ultra-high cycle fatigue testing was proposed. An S-N fatigue test curve of 109 cycles was obtained, with an infinite life (109 cycles) confirmed at 118 MPa and 105 cycle level fatigue life confirmed at 216 MPa.
Keywords: · Very high cycle fatigue · Ultrasonic fatigue test · Gas metal arc welding · AA 6061-T6 · Plate specimen · Butt welding